Expression and clinical significance of CA9 and SEC61G in non–small cell lung cancer - Yu Luo; Dehe Chen; Yunxi Wu; Yi Cai; Gaoxiong Xiao; Dinghai He; Yanjun Bai; Li Jiang (Clinical and Investigative Medicine, 2026)
Abstract Background: Lung cancer is the malignancy with the highest mortality rate globally. This study aimed to investigate the expression of carbonic anhydrase IX ( CA9 ) and SEC61G in non-small cell lung cancer (NSCLC) tissues and adjacent lung tissues and to analyze the relationships of these genes with clinicopathological features to identify potential biomarkers and therapeutic targets. Methods: Bioinformatic analysis was performed using the TIMER, TCGA, and GTEx databases to evaluate the differential expression of CA9 and SEC61G in NSCLC. The associations of these genes with tumour stage were further analyzed via GEPIA. For experimental validation, immunohistochemistry was conducted on 50 NSCLC tissue samples and 37 adjacent tissue samples collected from our institution. Results: The expression levels of both CA9 and SEC61G were significantly higher in NSCLC tissues than in adjacent tissues. The expression of these genes was positively correlated with advanced T stage, lymph node metastasis, distant metastasis, and tumour stage. A significant positive correlation was also observed between CA9 and SEC61G expression in NSCLC tissues. Conclusion: CA9 and SEC61G are upregulated in NSCLC, and their expression correlates with aggressive clinicopathological features, suggesting their involvement in tumour progression. The coexpression of these genes suggests a potential synergistic effect in NSCLC, adding to the existing evidence of their utility as significant indicators for predicting disease stage and prognosis.